SCREENING OF THE RESISTANT PEA CALLUS (PISUM SATIVUM L.) SELECTIVE MEDIA, CONTAINING FUSARIUM OXYSPORUM L. CULTURE FILTRATE - Tagimanova, D.S.; Rashidenova, Zh.A.; Khapilina , O.N. (Eurasian Journal of Applied Biotechnology, 2013)
Pea is the main legumes, which is widely cultivated in the Republic of Kazakhstan. To create new diseases-resistant and productive varieties, there should be applied methods of biotechnology, including the cell selection. In the selection process, which is carried out in vitro, there is conducted selection of cell populations that are resistant to the selective factor and then the whole plants are regenerated. The cultivation of peas in the region is associated with high affection by fungi and pests on the background of alternating droughts. Pea crop losses from pests and diseases can reach more than 30-50%. Root rot, ascochyta-leaf spot, false mildew, gray mold, powdery mildew, Fusarium blight, rust and bacterial blight are the most dangerous diseases for peas in Kazakhstan. Fusarium is dangerous in particular, because its injury is reinforced by the drought. The aim of the research is isolation of a typical strain of fungi of the Fusarium genus and optimization of pea callus on selective media containing culture filtrate of the pathogen. As the objects of the study the mature seeds of Omskiy Neosypayushchiisya pea varieties and promising hybrid breeding lines AI Baraev SPC of GF are used. The impact of exogenous hormones and concentration of the culture filtrate on kallus- formated ability and a weight of calluses was determined by optimization of culture conditions in vitro. As a result, the strain of the fungus Fusarium oxysporum FG-4 was isolated. Culture filtrate of this strain was added to the medium to induce callus formation and used for carrying out screening in vitro resistant callus peas. The optimal concentration of the filtrate in selective medium for formation of the calli of pea was determined. It was revealed that the optimal concentration for callus formation in selective conditions is the content of 5-10% of the culture filtrate, and the frequency of callus formation is 40-65%, which in the future to get morphogenic structures and induce organogenesis.